Positive Psychology Interventions: A Review for Counselling Practitioners - Lambert D'raven, Louise; Pasha-Zaidi, Nausheen (Canadian Journal of Counselling and Psychotherapy, 2014)
Positive psychology is focused on the prevention of mental health disorders, promotion of mental health, and treatment of distress via positive psychology interventions (PPIs). Effective in generating positive affect and experiences, PPIs alleviate depression and boost happiness in clinical and nonclinical populations. Geared toward counselling practitioners, the present article explores a sampling of PPIs such as savouring, gratitude, self-compassion, and capitalization. Why, how, and under what conditions these interventions are successful, and for whom they work are discussed. It is hoped that practitioners will use PPIs to enrich their work, contribute to the validation of the PPIs, and facilitate a true state of mental health for clients.